2020
DOI: 10.26656/fr.2017.4(5).067
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fruit and vegetable consumption among female university students

Abstract: The low intake of fruits and vegetables is a global issue. This research aimed to determine the association of fruit and vegetable intake with waist circumference and barriers of intake. A total of 279 female students from the International Islamic University Malaysia, Kuantan, were recruited through convenience sampling and provided with a set of questionnaires to identify their fruits and vegetable intake. The waist circumference of respondents was measured. The majority of students consumed only one serving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…An earlier study of 242 adults aged 18 and above in the state of Selangor reported an average consumption of FV of 173 grams per day, which was significantly lower than the recommended amount of 400 grams [19]. A more recent study by Ahmad Sirfan et al in a group of 279 young female students from a local public university revealed that approximately 87.8% of the respondents consumed fewer than 2 servings of fruits per day, while 93.6% consumed fewer than 3 servings of vegetables per day [20]. Another study by Eng and colleagues among 2,983 low-income adults residing in six low-cost flats in the Federal Territory of Kuala Lumpur also showed that 89.5% of the respondents did not meet the recommended daily intake of FV [21].…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study of 242 adults aged 18 and above in the state of Selangor reported an average consumption of FV of 173 grams per day, which was significantly lower than the recommended amount of 400 grams [19]. A more recent study by Ahmad Sirfan et al in a group of 279 young female students from a local public university revealed that approximately 87.8% of the respondents consumed fewer than 2 servings of fruits per day, while 93.6% consumed fewer than 3 servings of vegetables per day [20]. Another study by Eng and colleagues among 2,983 low-income adults residing in six low-cost flats in the Federal Territory of Kuala Lumpur also showed that 89.5% of the respondents did not meet the recommended daily intake of FV [21].…”
Section: Discussionmentioning
confidence: 99%
“…Some regional studies identified a series of common barriers for vegetable consumption, such as: the general dislike of taste [10,84], the considerable lack of time needed for shipping or cooking [10,21], picky children [10], high costs of purchasing sustainably produced vegetables [10,21], limited availability of fresh vegetables and high availability of other foods [21,84] for the healthy food categories, vegetables included, as one of the main barriers in front of their availability, an idea also supported by research [39]. Pocol et al [96] claim that young adults from Romania, Bulgaria, and Moldova need dietary education for developing a long-term sustainable food pattern and that gender is an important factor in choosing a sustainable diet.…”
Section: Hypothesismentioning
confidence: 99%
“…Several authors promote a direct attitude towards the need for a shift in the global dietary patterns [5,8,21,22,84], stating the obvious, namely: the low intake of fruits and vegetables and the high intake of meat can lead to chronic diseases. Additionally, through their studies, they propose alternatives to the current consumption patterns.…”
mentioning
confidence: 99%
“…Nearly 63% of university students have unhealthy eating habits, including low intake of fruits, vegetables, fish, whole grains, and legumes (4). Many studies reported that students do not follow the dietary standards' healthy eating recommendations as suggested by experts (5).…”
Section: Introductionmentioning
confidence: 99%